DEVELOPMENT OF EMOTIONAL INTELLIGENCE IN HIGH SCHOOL STUDENTS (Proceedings of International Educators Conference, 2023)
It is known that emotional intelligence is a highly developed ability of a person to understand his own emotions and the emotions of other people, and to manage them is likely to cause.